PERSPEKTIF baru penulisan sejarah indonesia / Penerjemah, Masri Maris; Editor, Henk Schulte Nordholt, Bambang Purwanto dan Ratna Saptari - BAMBANG Purwanto; MASRI Maris; NORDHOLT, Henk Schulte; RATNA Saptari (Yayasan Pustaka Obor Indonesia, 2013)
xiv, 446 hlm. : Ilus. : 24 cm.